Does social support improve self-management among rural hypertensive patients? An empirical analysis based on generalized propensity score matching - Li, Jiantao; Zhang, Jingru; Wang, Yuxiao; Zhang, Hanwen; Ma, Yangyang (Frontiers in Public Health, 2025)
BackgroundThis study aimed to examine the causal effect between perceived social support and self-management in rural patients with hypertension and to provide a basis for improving self-management.MethodsA cross-sectional study of 1,091 rural hypertensive patients in Shanxi Province was conducted from March through June 2022 to analyze the factors influencing social support as well as the causal effects of social support and self-management using generalized propensity score matching.ResultsRural hypertensive patients had a low level of social support (social support score = 0.632 ± 0.178). Social support had a significant and inverted U-shaped relationship with self-management; with increasing social support levels, the levels of self-management first rose and then declined, with an inflexion point of 0.774. Social support had significant negative correlations with sex, age, number of child, living status (i.e., living alone or living with others), disease duration, family economic status, and decision-making power, and positive correlations with having a spouse and having medical insurance.ConclusionGreater emphasis should be placed on the older adult, individuals living alone, those without spouses, only children, economically disadvantaged populations, and uninsured individuals to enhance the social support they received and ultimately improve their self-management of hypertension. Furthermore, establishing social support systems that are congruent with rural relational networks is crucial for promoting effective hypertension self-management.